Supporting Annotation as a Scholarly Tool—Experiences From the Online Chopin Variorum Edition. - Bradley, John; Vetch, Paul (Literary & Linguistic Computing, 2007)
In a meeting at King's College London in May 2000, John Unsworth proposed a list of seven 'scholarly primitives' which he claimed were 'self-understood' functions forming the basis for 'higher-level scholarly projects, arguments, statements [and] interpretations' (Unsworth, 2000). He claimed that his list summarized activities that were 'basic to scholarship across eras and across media', and went on to say that an analysis of these scholarly primitives might result in a clearer sense of how computing tools could support the scholarly endeavour. Here we focus on the primitive that was second on Unsworth's list, after 'Discovering': 'Annotation'. Our work on annotation arises out of a developing awareness that established Humanities Computing (HC) areas of interest, do not seem always to connect with the actual process of the research work being carried out by most humanists. We claimed in Bradley (2005) that a fundamentally different usage paradigm than those in operation in established HC was necessary to even notice, and then follow-up on, the potential of scholarly annotation as a computer-supported activity. This article presents our experiences, and the eventual outcomes, of the process of developing annotations tools for the Online Chopin Variorum Edition project (OCVE).' Beginning with a brief overview of activities related to annotation in Humanities Computing and Computing Science, we introduce the visible parts of the OCVE project, and address some discussion to the structures behind the scenes that support what it does, reporting what worked and what did not. We conclude by analysing the significance of our findings and describing the direction we think our annotation tool will take.